2004
DOI: 10.1074/jbc.m305645200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Multiple Drug Resistance Protein 1 in Neutral but Not Acidic Glycosphingolipid Biosynthesis

Abstract: MDR1a, 1b, MRP1) mouse fibroblasts showed the same loss of neutral glycosphingolipid (glucosyl ceramide, lactosyl ceramide) but not ganglioside (GM3) synthesis, confirming the proposed role for MDR1 translocase activity. Cryo-immunoelectron microscopy showed MDR1 was predominantly intracellular, largely in rab6-containing Golgi vesicles and Golgi cisternae, the site of glycosphingolipid synthesis. These studies identify MDR1 as the major glucosyl ceramide flippase required for neutral glycosphingolipid anaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 73 publications
4
111
1
Order By: Relevance
“…It has been suggested that the multiple drug resistance pump, MDR1, is the GlcCer flippase in the Golgi apparatus, but other proteins might also be involved. However, inhibition of MDR1 by cyclosporin A inhibits LacCer and globotriaosyl ceramide synthesis, but not ganglioside synthesis [59]. This suggests that neutral and acid GSLs are synthesized from distinct precursor GSL pools.…”
Section: Glccer Synthase (Gcs) (Reaction X)mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that the multiple drug resistance pump, MDR1, is the GlcCer flippase in the Golgi apparatus, but other proteins might also be involved. However, inhibition of MDR1 by cyclosporin A inhibits LacCer and globotriaosyl ceramide synthesis, but not ganglioside synthesis [59]. This suggests that neutral and acid GSLs are synthesized from distinct precursor GSL pools.…”
Section: Glccer Synthase (Gcs) (Reaction X)mentioning
confidence: 98%
“…There is some controversy about the molecular identification of the flippase responsible for transbilayer movement of GlcCer [59]. It has been suggested that the multiple drug resistance pump, MDR1, is the GlcCer flippase in the Golgi apparatus, but other proteins might also be involved.…”
Section: Glccer Synthase (Gcs) (Reaction X)mentioning
confidence: 99%
“…Glucosylceramide synthesized on the cytosolic surface of the cis-Golgi, which utilizes a different pool of ceramide, spontaneously translocates across the membrane to be converted to lactosylceramide and the ganglioside GM3. Translocation to the lumen of the trans-Golgi via the ABC transporter MDR1 may be specific for a glucosylceramide pool destined for the synthesis of neutral glycolipids [42]. PM, plasma membrane.…”
Section: Sphingolipid/cholesterol Domains and Sortingmentioning
confidence: 99%
“…Subsequent study showed that structurally diverse P-gp antagonists such as tamoxifen, verapamil, and cyclosporin A, inhibited GC synthesis in multidrug-resistant cancer cells (19). This observation was supported by De Rosa et al (20) in a study using cyclosporin A and ketoconazole in P-gp-containing cell lines. Furthermore, the study of Shabbits and Mayer (21) demonstrated that P-gp can modulate cellular sensitivity to endogenously generated longchain ceramide in response to taxane exposure.…”
Section: Introductionmentioning
confidence: 80%